Burial Mounds in Croatia. Landscapes of Continuity and Transformation - Potrebica, Hrvoje (2011)
Burial mounds act as agents in relation between prehistoric communities and landscape and play crucial role in claiming, gaining and preserving control over landscape implemented by such communities through notions of identity and continuity. This paper addresses transformation of that role from early to late prehistoric periods in different areas of Croatia, based on chronological difference between the burial mounds in continental and coastal area. Mounds in coastal areas appear as early as the Early Bronze Age, while in continental areas they appear only in the Early Iron Age with rather abrupt break in the middle of the last millennium B.C. and very short reappearance in the Roman period. Size, number and distribution of burial mounds was mostly determined by factors within the social framework of specific communities, which is in limited scope reflected in their content. Politics of use and re-use of burial mounds in periods following their initial construction is even more interesting in cases when we can establish sequence of culturally and/or ethnically different communities in the same area ; or large time span between two major occupation periods.
Projekt MZOS
ENG